Physical Exercise as Personalized Medicine for Dementia Prevention? - Müllers, Patrick; Taubert, Marco; Müller, Notger G. (Frontiers in Physiology, 2019)
Accumulating evidence supports the notion that lifestyle factors and physical activity can induce neuroplasticity in older adults and, thereby, modulate potential risk factors of dementia. However, a detailed look at the study results often reveals a wide interindividual variability. These may originate from the fact that there are “responders” and “non-responders” with respect to the impact of physical training on the brain. Furthermore, this high degree of interindividual variability suggests that physical training should not follow a “one size fits all” strategy. Instead based on the known individually varying response to physical training on physiological outcome parameters (i.e. VO2peak) we suggest that training should be tailored to an individual’s strengths and weaknesses by adapting the exercises to individual performance levels regarding both quality (i.e. type of exercise) and quantity (i.e. exercise intensity, duration, volume). We hypothesize that this personalized training is superior to classical fitness training in inducing neuroplasticity and in preventing neurodegeneration.